Manajemen Perubahan Dan Mitigasi Resistensi - Wilda Alfika; M Bahrul Ulum; Ansori Ansori (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze the concept of change management and resistance mitigation strategies in organizations through an integrative literature review approach. The study is motivated by the importance of organizational capability in responding to technological developments, public demands, and dynamic environmental changes. The method used is an integrative literature review based on academic books, national journal articles, and relevant scientific publications. The findings indicate that change management is a planned process undertaken by organizations to move from the current condition to a more effective and adaptive state. Resistance often emerges from individuals and organizational systems during the change process. Resistance mitigation can be implemented through effective communication, stakeholder participation, transformational leadership, training programs, and organizational culture strengthening. Therefore, successful organizational change depends on the ability to manage resistance systematically and sustainably.